Place Branding, an application to Sardinia. What is the perception of the brand and what is the difference between internal and external stakeholders? - Battaglia, Gian Mario; Dianová, Markéta; Hanzlík, Jan, 1979-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This research aims at drawing an extensive literature review of Place Branding, focusing on the relationship between Place Identity and Place Branding, which results in participatory place branding. Then, applying previous studies about Place Brand Personality this study measures the perception that internal and external stakeholders have of Sardinia. A scale developed by Kim et. Al (2013) has been used to measure it, based on five personality dimensions: Leadership, Excitement, Sophistication, Tradition, Peacefulness. A survey distributed to 200 Sardinians and 202 non-Sardinians. The results showed positive scores in Excitement, Peacefulness, and Tradition; tending to neutral as for Sophistication; negative in Leadership. There are statistical differences between the perception of the two groups, but they do not present contrasting views. Overall, the research presents the region as a place perceived mostly as touristic, as not attractive for investment, and somewhat attractive as a place of origin (export) and as a place to live
Vedoucí práce: Markéta Dianová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses